Sound HIV knowledge and common misconceptions about HIV among university students - Ibrahim, Normala; Jamil@Osman, Zubaidah; Hussin, Nik Shaliza; Awang, Hamidin; Naing@Noorjan, Khin Ohnmar; Ismail, Siti Irma Fadhilah; Amir Shapuddin, Fadzlina; Aziz, Rohani; Kho, Puay Bee; Sulaiman, Mohd Roslan; Md. Zain, Azhar; Gyanchand Rampal, Lekhraj Rampal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2013)
The objective of the study was to determine the proportion of sound HIV knowledge and common misconceptions about HIV among university students. A set of pre tested and validated questionnaire assessing sound HIV knowledge and common misconceptions about HIV was used in this cross sectional study. HIV knowledge was defined as sound when one was able to identify correctly two ways of preventing the sexual transmission of HIV and reject three major misconceptions about HIV. Out of 300 respondents, 298 completed the questionnaire giving a response rate of 99.3%. A total of 40.9% of university students have sound HIV knowledge. The majority of those who lacked sound HIV knowledge were young (60.2%) and female (60.4%). A significant proportion still believed that HIV can be transmitted via social contact (13.8%), by sneezing or coughing (11.4%) and mosquito bites (10.1%). About 6.7% were believed wrongly that HIV can be treated by vaccine and healthy-looking people cannot have HIV.